Characterization of Antigenic Property of Adult Spirocerca lupi Collected from Esophageal Nodules in Dogs - Rajapakse, Jayanthe; Wijekoon, Suranji; Silva, Niranjala De; Wijayawardhane, Nayana; Munasinghe, Madura (Indian Journal of Veterinary Sciences and Biotechnology, 2021)
Spirocerca lupi, the esophageal nematode of dog , causes a potentially fatal disease in domestic dogs. Immunological techniques can identify the parasite proteins which elicit an immune response. However, the antigenic properties of S. lupi adult worms have not been fully understood. The immuno-reactivity of the naturally infected dog sera with the S. lupi somatic antigens showed 7 prominent immunoreactive bands of distinct sizes at 199, 148, 100, 87, 49, 16, and 12 kDa, whereas 8 prominent bands at 230, 200, 100, 60, 49, 29, 16, and 12 kDa against hyper immune serum raised in the rabbits. Common antigen bands for both types of serum were observed at 100, 49 , 16 and 12 kDa. Intriguingly, the current study was able to indicate the detailed antigenic profile with specific molecular moieties which might be a manifesto for future investigation. Identified specific antigens merit further analysis as potential tools for the evaluation of treatment success and prognosis of spirocercosis, and development of a sensitive and specific diagnostic test for early detection of S. lupi in infected dogs